2023
DOI: 10.1186/s12964-023-01171-8
|View full text |Cite
|
Sign up to set email alerts
|

Islets in the body are never flat: transitioning from two-dimensional (2D) monolayer culture to three-dimensional (3D) spheroid for better efficiency in the generation of functional hPSC-derived pancreatic β cells in vitro

Abdoulaye Diane,
Layla Ibrahim Mohammed,
Heba H. Al-Siddiqi

Abstract: Diabetes mellitus (DM), currently affecting more than 537 million people worldwide is a chronic disease characterized by impaired glucose metabolism resulting from a defect in insulin secretion, action, or both due to the loss or dysfunction of pancreatic β cells. Since cadaveric islet transplantation using Edmonton protocol has served as an effective intervention to restore normoglycaemia in T1D patients for months, stem cell-derived β cells have been explored for cell replacement therapy for diabetes. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
2
0
0
Order By: Relevance
“…The copyright holder for this preprint this version posted June 18, 2024. ; https://doi.org/10.1101/2024.06.17.599254 doi: bioRxiv preprint 12 cells are absent [50,51]. This is further supported by the fact that we did not observe GIP-induced insulin secretion at low glucose in human islets in both this and a previous study [12].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted June 18, 2024. ; https://doi.org/10.1101/2024.06.17.599254 doi: bioRxiv preprint 12 cells are absent [50,51]. This is further supported by the fact that we did not observe GIP-induced insulin secretion at low glucose in human islets in both this and a previous study [12].…”
Section: Discussionsupporting
confidence: 85%
“…As recently reported for the newly established non-proliferative human beta-cell line EndoC-βH5 [26], we found that GIP acutely augmented insulin secretion at high glucose (20 mM) over a range of supraphysiological doses and modestly increased insulin secretion at low (2 mM) glucose. The increase in insulin secretion at low glucose may reflect that the tight regulation of beta-cell function is lost in 2D culture with a single islet cell type where paracrine signals from the delta and alpha 12 cells are absent [50,51]. This is further supported by the fact that we did not observe GIP-induced insulin secretion at low glucose in human islets in both this and a previous study [12].…”
Section: Discussionsupporting
confidence: 82%